Analisis Pendapatan Petani Ubi Alabio (Dioscorea alata) Di Desa Nelayan Kecamatan Sungai Tabukan Kabupaten Hulu Sungai Utara Propinsi Kalimantan Selatan - Mahdalena Mahdalena (Rawa Sains: Jurnal Sains STIPER Amuntai, 2012)
Agricultural development is aimed at increasing farmers' income and the role of agriculture in overall national development. Among the economic sectors, agriculture must remain the cornerstone of the development of the Hulu Sungai Utara district. The potential of the agricultural sector in Hulu Sungai Utara district includes rice and beans, corn, peanuts, sweet potatoes or sweet potato alabio which are more dominant. The objectives of this study were: (i) to find out the cost and acceptance of the alabio yam farmers for one farm, (ii) to find out how the alabio sweet potato contributes to farmers' income during one farm, (iii) to know the problems faced by farmers. This research has been carried out in the Tabukan Sub-District Fishermen Village, Hulu Sungai Utara Regency, from April to May 2009. While the data collection method is a direct interview method with farmers who are assisted by sample respondents using a questionnaire. At the alabio cassava farm in Desa Nelayan the average cost is Rp. 343,702.8, - / farming. The average income earned is Rp 2,439,036, 11, - and the average income is Rp 2,095,333.3, with an average contribution of 17.6%. Alabio yam farming in Desa Nelayan is a side activity, traditionally cultivated with a small scale of work. The selling price of the alabio perilogram in Nelayan Village ranges from Rp. 4,000 to Rp. 7,000.